Introductory Notes on Mental Health, Job Satisfaction and Personality of Teacher Educartors in Self-Financed College: Exploring the Impact of Working Conditions on Teacher Educators in Self-Financed Colleges (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Teaching is constantly a dynamic endeavour. It reveals a universe of information, experience,education, and expertise. No change can be successful without the cooperation and active participationof teachers, according to the International Commission on Education's 1996 report. It is said that nationcan rise the level of it’s teachers. This means that the standing of the teacher reflects the socio-culturalethos of a society. The community and the government should work to foster the conditions that willencourage and inspire teachers in positive and innovative ways. Hence there is a need of thorough studyof the conditions under which the teacher educators are working in various TEPs and the condititionsthat appear to affect the competence and performance of teacher educator.